2017
DOI: 10.1152/ajplung.00206.2017
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of oxytocin administration in obstructive sleep apnea

Abstract: Activation of oxytocin receptors has shown benefits in animal models of obstructive sleep apnea (OSA). We tested if nocturnal oxytocin administration could have beneficial effects in OSA patients. Eight patients diagnosed with OSA were administered intranasal oxytocin (40 IU). Changes in cardiorespiratory events during sleep, including apnea and hypopnea durations and frequency, risk of event-associated arousals, and heart rate variability, were assessed. Oxytocin significantly increased indexes of parasympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Thus, intranasal OT application had been tested in heart rate variability-an index of autonomic cardiac control (Quintana et al, 2013). Although intranasally-applied OT usually does not evoke significant change in plasma OT levels (Leng and Ludwig, 2016), it could exert antiarrhythmic effect in human being as reported (Jain et al, 2017; Sack et al, 2017).…”
Section: Limitation For Therapeutic Use Of Otmentioning
confidence: 99%
“…Thus, intranasal OT application had been tested in heart rate variability-an index of autonomic cardiac control (Quintana et al, 2013). Although intranasally-applied OT usually does not evoke significant change in plasma OT levels (Leng and Ludwig, 2016), it could exert antiarrhythmic effect in human being as reported (Jain et al, 2017; Sack et al, 2017).…”
Section: Limitation For Therapeutic Use Of Otmentioning
confidence: 99%
“…Studies diverge between no impact of intranasal oxytocin on HR 60 – 63 and decreased HR in pregnant women during oxytocin infusions 64 . Studies on HRV have reported intranasal oxytocin-induced increases at rest in healthy subjects 59 , 60 , patients with obstructive sleep apnoea 65 , in pregnant women after oxytocin infusion 64 , decreases during exposure to stress 66 , 67 or no effects at rest in both healthy individuals 63 , 66 and in men with Fragile X syndrome 68 . We have failed to detect any significant effects of a single dose of intranasal (40 IU) or intravenous infusion (10 IU) of oxytocin on HR or HRV in healthy men over an extended period of observation post dosing (14–104 min) 63 .…”
Section: Introductionmentioning
confidence: 99%
“…Using optogenetic tools to chronically activate this specific population of OT secreting PVN MCNs they prevented the development of hypertension. In line with this finding, Jain and coworkers [245] reported that intranasal OT administration in patients suffering from OSA reduces the frequency of hypopneas and Fig. (2).…”
Section: Vp and Ot In Hypertensionmentioning
confidence: 52%